Analisis Semiotika Roland Barthes terhadap Representasi Visual dalam Poster Drama Korea Hospital Playlist - Sasikirana, Aulia Nabila; Ghanistyana, Lathifa Prima; Fitria, Jihan; Purnama, Bakti (Riwayat: Educational Journal of History and Humanities, 2025)
The advancement of visual media as a promotional tool extends beyond commercial advertising into the realm of health-themed entertainment. A notable example is the promotional poster of the Korean drama Hospital Playlist, which portrays the medical profession in a warm and emotionally resonant manner. This study aims to explore the visual meanings conveyed in the poster by applying Roland Barthes semiotic theory, which interprets signs through two levels of meaning: denotation and connotation. The research employs a descriptive qualitative method with visual semiotic analysis, focusing on elements such as clothing colors, facial expressions, lighting, and the visual composition of characters. The findings reveal that these visual elements collectively construct a representation of medical professionals as approachable, collaborative, and empatheticcontrasting with the traditionally serious and rigid portrayal of the medical field. The diversity in clothing colors symbolizes the unique traits of each character, while their expressions and gestures communicate themes of warmth and familial bonds. This study highlights how entertainment media can function as an effective tool for visual communication, shaping positive public perceptions of the medical profession, particularly among younger audiences.